Carbohydrate-based peptidomimetics targeting neuropilin-1: Synthesis, molecular docking study and in vitro biological activities. Issue 21 (1st November 2016) - Richard, Mylène; Chateau, Alicia; Jelsch, Christian; Didierjean, Claude; Manival, Xavier; Charron, Christophe; Maigret, Bernard; Barberi-Heyob, Muriel; Chapleur, Yves; Boura, Cédric; Pellegrini-Moïse, Nadia
Graphical abstract: Abstract: Neuropilin-1 (NRP-1), a transmembrane glycoprotein acting as a co-receptor of VEGF-A, is expressed by cancer and angiogenic endothelial cells and is involved in the angiogenesis process. Taking advantage of functionalities and stereodiversities of sugar derivatives, the design and the synthesis of carbohydrate based peptidomimetics are here described. One of these compounds (56 ) demonstrated inhibition of VEGF-A165 binding to NRP-1 (IC50  = 39 μM) and specificity for NRP-1 over VEGF-R2. Biological evaluations were performed on human umbilical vein endothelial cells (HUVECs) through activation of downstream proteins (AKT and ERK phosphorylation), viability/proliferation assays and in vitro measurements of anti-angiogenic abilities.